A reinforcement learning approach to optimal part flow management for gas turbine maintenance. (February 2020) - Compare, Michele; Bellani, Luca; Cobelli, Enrico; Zio, Enrico; Annunziata, Francesco; Carlevaro, Fausto; Sepe, Marzia
We consider the maintenance process of gas turbines used in the Oil and Gas industry: the capital parts are first removed from the gas turbines and replaced by parts of the same type taken from the warehouse; then, they are repaired at the workshop and returned to the warehouse for use in future maintenance events. Experience-based rules are used to manage the flow of the parts for a profitable gas turbine operation. In this article, we formalize the part flow management as a sequential decision problem and propose reinforcement learning for its solution. An application to a scaled-down case study derived from real industrial practice shows that reinforcement learning can find policies outperforming those based on experience-based rules.